Identification of therapeutic targets in lung adenocarcinoma using Mendelian randomization and multi-omics - Yue Li; Keru Ma; Hao Wang; Zongying Liu; Zhuying Li (Discover Oncology)
Abstract Background Lung adenocarcinoma (LUAD) remains associated with limited effective pharmacological treatment options. This study aimed to identify potential therapeutic targets for LUAD through the integration and analysis of multi-omics datasets. Methods A meta-analysis was conducted using two extensive proteomics datasets, the UK Biobank Proteomics Project (UKB-PPP) and the Fenland study, to identify disease-associated targets for LUAD through the Summary-Data-Based Mendelian Randomization method. Sensitivity analysis, including heterogeneity tests for dependent instruments, were conducted to validate the findings. The prognostic relevance of the identified candidate targets was assessed using transcriptomic data. Functional interactions were explored via protein–protein interaction network analysis, while single-cell analyses were employed to determine cell-specific expression patterns and differentiation trajectories. Potential side effects and therapeutic indications of these targets were evaluated using phenome-wide association studies and pharmacological data mining. Results Following meta-analysis, a primary significant target, intercellular adhesion molecule 5 (ICAM5), along with potential targets FUT8 and KLK13, were identified as therapeutic candidates for LUAD. FUT8 demonstrated a positive association with LUAD risk (OR = 1.02, p = 0.049), while ICAM5 (OR = 0.88, p = 0.002) and KLK13 (OR = 0.85, p = 0.021) exhibited negative associations. ICAM5 was further identified as an independent prognostic factor for patient survival (HR: 0.788, 95% CI: 0.663–0.936, p = 0.007) and revealed significant diagnostic and prognostic utility in LUAD. ICAM5 expression correlated with various immune infiltration patterns, suggesting potential modulation of the tumor immune microenvironment. Single-cell analysis revealed that ICAM5 did not directly impact LUAD cell differentiation, though its downstream target, MUC1, may contribute to differentiation processes, particularly in KRAS-mutated LUAD. Furthermore, phenome-wide association studies did not reveal substantial evidence of adverse phenotypes linked to ICAM5, supporting its safety profile for drug development. Conclusion ICAM5 emerges as a promising biological marker with significant prognostic and therapeutic potential in LUAD.